Development programs, change readiness and work performance of young managers in Malaysia - Juhdi, Nurita; Juhdi, Noor Hasni (ABM Publications, 2020)
The objective of the study was to test the mediating effect of change readiness on the relationship between management development programs and the work performance. Four development programs were examined namely on-the-job programs, off-the-job programs, assessment and mentoring. The respondents were all below 45 years old and they are either performing professional occupations or in low to middle level positions. All of them had participated in development programs. Three hundred and ninety-nine employees participated in the study. The results showed that change readiness was the sole significant predictor for work performance and it served as a partial mediator between management development programs and work performance. The findings provides support to the adult learning theory and offers clearer perspective in the area of talent management specifically in succession planning. The study suffers from two limitations; the data analysis was based on self-reported views by the employees and the low R2 values yielded in the regression analysis which was only 32.4 percent.